2019
DOI: 10.1111/nin.12311
|View full text |Cite
|
Sign up to set email alerts
|

Power distance and migrant nurses: The liminality of acculturation

Abstract: A dearth of literature focuses on the relationship between acculturation, power distance and liminality for migrant nurses entering foreign workplaces. Expectations are for migrant nurses to be practice‐ready swiftly. However, this aspiration is naïve given the complex shifts that occur in deeply held cultural beliefs and practices and is dependent on an organisational climate of reciprocal willingness to adapt and learn. This exploratory study identified that although a plethora of literature addresses challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…Third, it answers the call in recent work to test the boundary conditions of the ethical leadership effect (Choi et al, 2019). Specifically, this study tested the moderation role of power distance.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…Third, it answers the call in recent work to test the boundary conditions of the ethical leadership effect (Choi et al, 2019). Specifically, this study tested the moderation role of power distance.…”
Section: Introductionmentioning
confidence: 63%
“…Like prior studies’ results, power distance affects people’s sensitivity to the ethical behavior of leaders. Nurses who work in high-power distance contexts will pay more attention to the ethical behaviors of the leader, and they will be greatly encouraged by the leader’s self-discipline and by management policies emphasizing fairness, which will, in turn, influence their work attitudes and behaviors (Choi et al, 2019). The results showed that power distance significantly moderated the relationship between ethical leadership and psychological mediating variables; for nurses who perceive high-power distance, ethical leadership had a more obvious influence on psychological safety (Peltokorpi, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the years, important cross‐cultural research has been undertaken on nurses’ competencies or attitudes in their home countries, such as the ETHAN Project, Hart and Mareno (2013) or Martinez and Martinez (2002), cultural differences between Spanish and UK nurses and the importance of caring (Watson et al, 2003) and perceptions of nurses from both countries (Watson et al, 2002). However, in spite of some emerging findings such as Gea‐Caballero’s about Spanish nurses who plan to emigrate in a near future as a consequence of globalization, there is very little scientific understanding of what these competencies and needs involve or mean in their host countries and how these migrant nurses perceive them once they work or have worked in those countries (Choi et al, 2019; Cowan et al, 2007; Moyce et al, 2016). Although statistics and sociology have investigated the migration in a general context throughout history (Villani et al 2016), analysing the evolutionary profile of Spanish migrants to the UK since the 1960s (Morgan, 2016), it is essential to thoroughly consider these Spanish nurses’ experiences and perceptions of practising in the UK, in terms of exploring their reasons for and neediness of moving as it has been suggested previously for foreign nurses (Lee, 2016).…”
Section: Introductionmentioning
confidence: 99%